2013
DOI: 10.1128/iai.01406-12
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Induced Disruption of Monolayer Permeability and Proinflammatory Cytokine Secretion in Polarized Human Gastric Epithelial Cells

Abstract: cHelicobacter pylori infection of the stomach is related to the development of diverse gastric pathologies. The ability of H. pylori to compromise epithelial junctional complexes and to induce proinflammatory cytokines is believed to contribute to pathogenesis. The purpose of this study was to use an in vitro human gastric epithelial model to investigate the ability of H. pylori to affect permeability and the extent and polarity of the host inflammatory response. NCI-N87 monolayers were cocultured with live or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 36 publications
(40 reference statements)
2
56
0
Order By: Relevance
“…We speculate that the vir B4 – strain, in which the assembly of T4SS is inactivated, is forming a defective T4SS resulting in an altered presentation of T4SS components or even of other surface molecules like LPS to TLRs, hence causing an altered induction of inflammatory mediators. In agreement with this, a recent study reported that epithelial cells challenged with heat killed H. pylori (no activity of the T4SS) induced significantly more cytokines than live cagPAI strains (exhibiting a functional T4SS), and authors also suggested this might be due to change in presentation of surface antigens like LPS to epithelial cells [33]. IL1ÎČ has been described as an autocrine survival factor or a paracrine product of neutrophils stimulated with lipopolysaccharide (LPS), producing a more effective inflammatory response [34].…”
Section: Discussionsupporting
confidence: 68%
“…We speculate that the vir B4 – strain, in which the assembly of T4SS is inactivated, is forming a defective T4SS resulting in an altered presentation of T4SS components or even of other surface molecules like LPS to TLRs, hence causing an altered induction of inflammatory mediators. In agreement with this, a recent study reported that epithelial cells challenged with heat killed H. pylori (no activity of the T4SS) induced significantly more cytokines than live cagPAI strains (exhibiting a functional T4SS), and authors also suggested this might be due to change in presentation of surface antigens like LPS to epithelial cells [33]. IL1ÎČ has been described as an autocrine survival factor or a paracrine product of neutrophils stimulated with lipopolysaccharide (LPS), producing a more effective inflammatory response [34].…”
Section: Discussionsupporting
confidence: 68%
“…However, these results were not confirmed in another study which showed no change of ZO‐1 protein expression level irrespective of H pylori infection or the presence of CagA . Previous TEER studies with H pylori infection of gastric cancer epithelial cell lines, N87 and MKN28, showed that while wild‐type H pylori infection decreased epithelial barrier function (ie, TEER), TEER was also reduced by cagA , cagE , vacA , and urease B knockout strains (ie, the TEER changes were independent of what are considered the main virulence factors) . For example, H pylori strain 26695 wt , and the vacA and the cagA mutant strains induced a significant TEER decreased at both 24 hours (691‐776 Ω cm 2 ) and 48 hours (436‐519 Ω cm 2 ) compared with uninfected monolayers (1110 and 11 096 Ω cm 2 ) .…”
Section: Discussionmentioning
confidence: 83%
“…In Figure B, we show that the TEER rapidly recovered even with TN2GF4 wild‐type infection consistent with the notion that the apical junctional complex of gastroid monolayers is robust and confirming that the TEER of gastroid monolayers was not altered by these virulence factors. The TEER range differs depending on the cell type; the maximum TEER reported has been 470 Ω cm 2 on mucosoid vs, 80‐1400 Ω cm 2 on conventional cell lines . Studies with conventional cell lines showed that TEER approximately dropped 30%‐50% permanently compared with base levels during 8‐48 hours co‐culture with H pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Most, but not all, in vitro studies have used nonpolarized gastric cancer cells or polarized nongastric cells [35,36]. In one interesting study, polarized cells were grown as monolayers, thus mirroring the in vivo condition in that H. pylori were able only to contact the apical surface [37].…”
Section: Cagamentioning
confidence: 99%